2020
DOI: 10.1002/hbm.25188
|View full text |Cite
|
Sign up to set email alerts
|

Birth weight is associated with adolescent brain development: A multimodal imaging study in monozygotic twins

Abstract: Previous research has shown that the prenatal environment, commonly indexed by birth weight (BW), is a predictor of morphological brain development. We previously showed in monozygotic (MZ) twins associations between BW and brain morphology that were independent of genetics. In the present study, we employed a longitudinal MZ twin design to investigate whether variations in prenatal environment (as indexed by discordance in BW) are associated with resting-state functional connectivity (rs-FC) and with structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 77 publications
1
10
0
Order By: Relevance
“…Rat experiments have shown that withdrawal of oxygen supply perinatally impairs behaviour and alters prefrontal dopamine (and other monoamine) levels in males more than females (Laplante et al, 2012;Amanda L. Smith et al, 2014). A human twin study found that birth weight discrepancy was linked with functional connectivity in the limbic network (lower birth weight-less efficient connectivity), an effect that was stronger in males compared to females (Hayward et al, 2020). Sex differences in microglial activation and inflammatory responses may underlie this male vulnerability to prenatal hypoxic-ischemic events (Mirza et al, 2015).…”
Section: Sex Differencesmentioning
confidence: 99%
“…Rat experiments have shown that withdrawal of oxygen supply perinatally impairs behaviour and alters prefrontal dopamine (and other monoamine) levels in males more than females (Laplante et al, 2012;Amanda L. Smith et al, 2014). A human twin study found that birth weight discrepancy was linked with functional connectivity in the limbic network (lower birth weight-less efficient connectivity), an effect that was stronger in males compared to females (Hayward et al, 2020). Sex differences in microglial activation and inflammatory responses may underlie this male vulnerability to prenatal hypoxic-ischemic events (Mirza et al, 2015).…”
Section: Sex Differencesmentioning
confidence: 99%
“…Typically, the general indicators can affect IQ scores, among which the prenatal environment is discussed previously [ 26 ]. The high pregnancy S/D value can predict fetal intrauterine distress and poor perinatal outcomes [ 27 ]; however, whether subtle variations in the routine ultrasound detection are associated with long-term cognitive and motor abilities is yet to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…This means that, on a greater number of occasions throughout the study, it was these heavier twins who showed greater cognitive skills (specifically: in task 1, at 18 and 24 months; in task 2, at 24 months; in task 3, at all the three ages studied). In the lighter twins, it could be that their developmental history-their less optimal intra-uterine environment which affected both their birth weight and brain development [36][37][38][39]-was being translated into their lower sensitivity to environmental information. Less complex neural circuits, due to their less optimal intra-uterine environment, would imply less complex mental activities, that is, a lesser capacity to focus their attention on the appropriate information in the task (less capacity to suppress the interference generated by color).…”
Section: Discussionmentioning
confidence: 99%
“…This twin is usually the most affected since they have a less optimal intra-uterine environment than their heavier birth weight twin, which ultimately affects both their birth weight and brain development [36][37][38][39]. Among other disadvantages the lighter twins face, the literature on the subject has shown that they have lower IQ; perform significantly worse in cognition, language, and motor skills compared to the heavier twins; and are usually at major risk for later behavior problems [37][38][39][40]. However, many aspects of these children's development are still unknown because, if we consider that the research on psychoeducational issues in twin children is scarce, even scarcer is the research focused on twin children with BWD.…”
Section: Twin Babies In Early Childhood Educationmentioning
confidence: 99%